Estimating Patient-Level Costs for Acute and Sub-Acute Inpatient Services in Thailand - Khiaocharoen, Orathai; Pannarunothai, Supasit; Riewpaiboon, Arthorn; Zungsontiporn, Chairoj (Siriraj Medical Journal, 2020)
Objective: To determine patient-level cost of acute and sub-acute inpatient services and to examine factors predicting cost for patients requiring sub-acute care. Methods: The study design was prevalence-based cost-of-illness approach. Subjects were 2,419 inpatients requiring sub-acute care in 2 regional hospitals. The costs of services were calculated employing standard costing methods. Inpatient costs were prospectively recorded from July 2008 to February 2009. Micro-costing approach was employed under a provider perspective. Paired-t test was used to evaluate the significant difference. Results: The average cost during the sub-acute phase was much lower than that in the acute phase (14,877 vs. 23,089 Baht). Nursing service constituted the highest cost (42.6%) in sub-acute phase, whereas direct rehabilitation costs was only 2%. Burn with low physical function had the highest average costs (67,243 Baht). The average cost was significantly higher than the average charge (p<0.001). The physical function at admission, Rehabilitation Impairment Category (RIC) and length of stay (LOS) were the key determinants of sub-acute service costs (adjusted R2 =0.688; p<0.001). Conclusion: The cost in sub-acute phase was lower than the cost in acute phase. Physical function, RIC and LOS could be used to predict cost of sub-acute inpatient services.